Phase transition kinetics and surface binding states of methylammonium lead iodide perovskite. Issue 10 (19th February 2016) - Rajendra Kumar, G.; Dennyson Savariraj, A.; Karthick, S. N.; Selvam, S.; Balamuralitharan, B.; Kim, Hee-Je; Viswanathan, K. K.; Vijaykumar, M.; Prabakar, Kandasamy
Abstract : We have presented a detailed analysis of the phase transition kinetics and binding energy states of solution processed MAPbI3 thin films prepared at ambient conditions and annealed at different elevated temperatures. Abstract : We have presented a detailed analysis of the phase transition kinetics and binding energy states of solution processed methylammonium lead iodide (MAPbI3 ) thin films prepared at ambient conditions and annealed at different elevated temperatures. It is the processing temperature and environmental conditions that predominantly control the crystal structure and surface morphology of MAPbI3 thin films. The structural transformation from tetragonal to cubic occurs at 60 °C with a 30 minute annealing time while the 10 minute annealed films posses a tetragonal crystal structure. The transformed phase is greatly intact even at the higher annealing temperature of 150 °C and after a time of 2 hours. The charge transfer interaction between the Pb 4f and I 3d oxidation states is quantified using XPS.